Impact of board composition towards corporate social responsibility disclosure / Hazizah Bujang Salleh - Bujang Salleh, Hazizah (2015)
Globalisation throughout the world has seen the emergence of corporate social responsibility (CSR) reporting among firms. CSR has become one of the strategies that firms can rely upon to sustain in the business world. This is due to the recognition that firms' existence depend on their ability to maintain good reputation while achieving maximum profit (Gustafon, 2002). CSR has also been regarded as a strategic mechanism used by firms in addressing international competition (Williams, 2003). Malaysian firms are not an exception to this scenario.